A monoallelic SEC23A variant E599K associated with cranio‐lenticulo‐sutural dysplasia. Issue 1 (28th September 2021) - Cisarova, Katarina; Garavelli, Livia; Caraffi, Stefano Giuseppe; Peluso, Francesca; Valeri, Lara; Gargano, Giancarlo; Gavioli, Sara; Trimarchi, Gabriele; Neri, Alberto; Campos‐Xavier, Belinda; Superti‐Furga, Andrea
Abstract: Cranio‐lenticulo‐sutural dysplasia (CLSD; MIM 607812) is a rare or underdiagnosed condition, as only two families have been reported. The original family (Boyadjiev et al., Human Genetics, 2003, 113, 1–9 and Boyadjiev et al., Nature Genetics, 2006, 38, 1192–1197) showed recessive inheritance of the condition with a biallelic SEC23A missense variant in affected individuals. In contrast, another child with sporadic CLSD had a monoallelic SEC23A variant inherited from the reportedly unaffected father (Boyadjiev et al., Clinical Genetics, 2011, 80, 169–176), raising questions on possible digenism. Here, we report a 2‐month‐old boy seen because of large fontanels with wide cranial sutures, a large forehead, hypertelorism, a thin nose, a high arched palate, and micrognathia. His mother was clinically unremarkable, while his father had a history of large fontanels in infancy who had closed only around age 10 years; he also had a large forehead, hypertelorism, a thin, beaked nose and was operated for bilateral glaucoma with exfoliation of the lens capsule. Trio genome sequencing and familial segregation revealed a monoallelic c.1795G > A transition in SEC23A that was de novo in the father and transmitted to the proband. The variant predicts a nonconservative substitution (p.E599K) in an ultra‐conserved residue that is seen in 3D models of yeast SEC23 to be involved in direct binding between SEC23 and SAR1 subunits of the coat protein complex II coat. This observation confirms the link between SEC23A variants and CLSD but suggests that in addition to the recessive inheritance described in the original family, SEC23A variants may result in dominant inheritance of CLSD, possibly by a dominant‐negative disruptive effect on the SEC23 multimer.